2013
DOI: 10.4049/jimmunol.1202307
|View full text |Cite
|
Sign up to set email alerts
|

CCL22-Producing CD8α− Myeloid Dendritic Cells Mediate Regulatory T Cell Recruitment in Response to G-CSF Treatment

Abstract: G-CSF prevents type 1 diabetes in the NOD mouse by promoting the local recruitment of T regulatory cells (Tregs). This is an indirect effect because adoptive transfer of G-CSF–induced tolerogenic dendritic cells (DCs) promotes Treg accumulation. However, the identity of the particular DC subset and the molecule(s) mediating this effect remain unknown. We demonstrate in this study that the adoptive transfer of CD11chighCD8α− DCs isolated from pegylated G-CSF (pegG-CSF) recipients, but not that of other DC subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…A causal variant within neutrophil cytosolic factor (NCF2) identified as a susceptibility gene in both childhood-and adult-onset SLE reduced the production of reactive oxygen species (ROS) and enhanced the susceptibility to lupus within patients [96]. This was similar to the association between loss of function polymorphisms in Ncf1 and RA [97][98][99][100][101]. On the other hand, ROS reduction due to Ncf1 deficiency delayed T1D in NOD mice [82], highlighting again the dichotomous function of genes regulating neutrophil activities.…”
Section: Neutrophils In T1d and Slesupporting
confidence: 55%
“…A causal variant within neutrophil cytosolic factor (NCF2) identified as a susceptibility gene in both childhood-and adult-onset SLE reduced the production of reactive oxygen species (ROS) and enhanced the susceptibility to lupus within patients [96]. This was similar to the association between loss of function polymorphisms in Ncf1 and RA [97][98][99][100][101]. On the other hand, ROS reduction due to Ncf1 deficiency delayed T1D in NOD mice [82], highlighting again the dichotomous function of genes regulating neutrophil activities.…”
Section: Neutrophils In T1d and Slesupporting
confidence: 55%
“…CCL22, a member of the CC chemokine families, is mainly produced by monocyte-derived macrophages and DCs upon stimulation with microbial products. 32,33 A recent study has reported that the mean serum levels of CCL22 in newly diagnosed patients with multiple sclerosis were significantly lower than those in treated patients with multiple sclerosis and healthy people, 20 suggesting that CCL22 serves as a biomarker for autoimmune diseases. However, the roles of CCL22 in the regulation of immune homeostasis by apoptotic cell clearance are poorly defined, although impairment of apoptotic cell phagocytosis causes autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Activation and antigen priming in secondary lymphoid organs promote downregulation of CCR7 and CD62L, whereas other memory/effector type trafficking receptors may be upregulated to allow Tregs to migrate into nonlymphoid or inflamed tissues (14,(17)(18)(19). To date, few chemokine receptors have been associated with the tumor homing properties of Tregs, although a role for CCL22 in the recruitment of CCR4 þ Tregs into human ovarian and/or breast cancer has been described (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%